Democracy in Brazil and its Implications for Human Rights - Santander, Carlos Ugo; Hissa, Carolina; Guimarães, Vanessa Coelho; Woyames, Aletheia (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The article explores, from the perspective of the theoretical-methodological framework of the quality of democracy, the recent developments regarding human rights, the disputes, challenges and prospects from the political context of the government of President Jair Bolsonaro in Brazil. The theoretical-methodological proposal is supported by political scientist Leonardo Morlino and this analytical model takes eight dimensions as reference: political participation, political competence, electoral accountability, interinstitutional accountability, rule of law, responsiveness, freedoms and solidarity/equality.